Consumers’ Inclusiveness and Migration: Evaluation of Selected Brands through the Brand Identity Prism - Obukoadata, Presly Ogheneruke; Uduma, Ngozi Eje; Obukoadata, Oluchi Sussan (Communication Today, 2021)
Brand identity management is central to brand building which prompted our evaluation on two master brands – Coca Cola and CloseUp – using the Brand Identity Prism. It explored how consumer inclusiveness and socioeconomic migration have affected consumers’ identification with the select brands. A survey based on the projective technique that deconstructed the six facets of the BIP as items in the questionnaire was applied to a cross national consumer-base of sample size 2,881 arrived at using 95% confidence level, 80% expected response rate and loss of sampling efficiency at 1.5. Data collected was analysed using the simple percentage and the Two-Way ANOVA Statistics to ascertain if there had been any significant difference among the means of the timeline. We argue that a brand might not have consistent strong identification with consumers over all the facets every time, and that with consumer inclusiveness and socio-economic migration, it is likely that consumers will stick with existing brands irrespective of lifestyles, new tastes and choices especially if majority of the brands’ facets through the prism are optimised. It is concluded that consumer inclusiveness and socio-economic migration have positive effects on consumer identification with identified brands despite the existence of inclusion and migration over a timeline.